Exploring the feasibility and acceptability of DIALOG+ (a structured digital communication tool) in strengthening psychiatric care in India and Pakistan: a qualitative pilot study - Sana Zehra Sajun; Victoria Jane Bird; Lakshmi Venkatraman; Padmavati Ramachandran; Aneeta Pasha; Renata Peppl; Onaiza Qureshi; Krishna Priya; Hufsa Sarwar; Kasthuri Divya; Mehwish Dawood; Syjo Davis; et al. (BMJ Open)
Objectives To assess the implementation feasibility and acceptability of a structured digital psychosocial communication tool (DIALOG+) to strengthen the quality of person-centric care in psychiatric settings within Pakistan and India.Design A hybrid inductive and thematic qualitative analysis using individual interviews (IDIs) and focus group discussions (FGDs).Setting Two psychiatric hospitals (Karwan-e-Hayat and Jinnah Postgraduate Medical Centre) in Karachi, Pakistan and one psychiatric care organisation (Schizophrenia Research Foundation) in Chennai, IndiaParticipants Interviews were conducted with 8 mental health clinicians and 40 patients who completed the DIALOG+ pilot as well as wider stakeholders, that is, 12 mental health clinical providers, 15 caregivers of people with psychosis and 13 mental health experts.Intervention A technology-assisted communication tool (DIALOG+) to structure routine meetings and inform care planning, consisting of monthly sessions over a period of 3 months. The intervention comprises a self-reported assessment of patient satisfaction and quality of life on eight holistic life domains and three treatment domains, followed by a four-step solution-focused approach to address the concerns raised in chosen domains for help.Outcome measures Key insights for the implementation feasibility and acceptability of DIALOG+ were assessed qualitatively using inductive thematic analysis of 22 IDIs and 8 FGDs with 54 individuals.Results Clinicians and patients ascribed value to the efficiency and structure that DIALOG+ introduced to consultations but agreed it was challenging to adopt in busy outpatient settings. Appointment systems and selective criteria for who is offered DIALOG+ were recommended to better manage workload. Caregiver involvement in DIALOG+ delivery was strongly emphasised by family members, along with pictorial representation and relevant life domains by patients to enhance the acceptability of the DIALOG+ approach.Conclusion Findings highlight that the feasibility of implementing DIALOG+ in psychiatric care is closely tied to strategies that address clinician workload. Promoting institutional ownership in strengthening resource allocation is essential to reduce the burden on mental health professionals in order to enable them to provide more patient-centric and holistic care for people with psychosis. Further research is required to explore the appropriateness of including caregivers in DIALOG+ delivery to adapt to communal cultural attitudes in South Asia.